Developing an English for Specific Purposes Voice-Over Course for a Blind Learner - Naufal Rangkuti; Setyarini, Sri (The Center for Disability Studies and Services Brawijaya University, 2024)
This study developed and evaluated an English for Specific Purposes (ESP) voice-over course tailored for a blind learner. Motivated by the need to make voice-over training accessible, the qualitative research focused on a 23-year-old blind university student. The course utilized non-visual methods, such as audio recordings, verbal instructions, and tactile tools, to teach vocal modulation, emotional expression, and clarity. Results showed significant improvement in the participant’s voice-over skills, including enhanced vocal modulation and emotional expression. Feedback indicated the course was effective but suggested adding more diverse practice scenarios and descriptive audio examples. The study contributes to inclusive education by demonstrating that specialized training programs can be adapted for blind learners. It provides a model for making voice-over work accessible and offers recommendations for applying the approach to other fields and assessing long-term impacts on professional development.